Identifying key performance indicators for marketing strategies in mobile applications: A systematic literature review - Reyes-Menéndez, Ana; Saura, José Ramón; Palos-Sánchez, Pedro R (International Journal of Electronic Marketing and Retailing, 2020)
In practice marketing can and should play an important role in mobile applications when formulating marketing strategies. The aim of this article is to identify the main KPIs to measure the effect of marketing strategies in mobile applications. To achieve this goal, we carried out a systematic literature review (SLR) on the topic of mobile applications and marketing strategies. The search terms consulted in the databases were KPIs, marketing and mobile applications obtaining a total of n = 1,088 studies. The databases consulted to extract data where Scopus, PubMed, PsyINFO, ScienceDirect and Web of Science. The results obtained in this research were the identification, development and analysis of the main quantitative and qualitative KPIs to measure the effect of marketing strategies in mobile applications. Furthermore, we name the main scientific journals developing further studies on this subject, as well as on the most relevant topics within the industry. The results of the research can be used to enhance mobile APP marketing strategy analysis and thus, enhance their development, both in the scientific and the professional sectors.
Keywords: mobile applications; marketing strategies; key performance indicators; KPIs; apps; marketing metrics; Scopus